Food availability to an Adamussium bed during the austral summer 1993/1994 (Terra Nova Bay, Ross Sea) - ALBERTELLI G; CATTANEO VIETTI R; CHIANTORE M; FABIANO M.; PUSCEDDU, ANTONIO (Journal of Marine Systems, 1998)
In the framework of the ROSSMIZE Project (Ross Sea Marginal Ice Zone Ecology) of the Italian Antarctic Research Programme (PNRA), the organic matter flux through the water column and its role on benthic communities have been taken in particular account. During the austral Summer 1993-1994, from December 27, 1993 to February 11, 1994, a study on this flux in shallow waters was carried out, in a station close to Terra Nova Bay Italian base (Ross Sea), at 40 m depth. This site reaches high values of density (60 ind/m2) and is characterized by the filter-feeding Adamussium colbecki, a scallop which biomass (120 g DW/m2). At the beginning of the sampling period, a sediment trap was positioned on the sea-bottom and samples were collected every 3-5 days, as well as temperature, salinity and fluorescence data from sea surface to bottom. Fluorescence profiles put in evidence a phytoplankton bloom occurring during the maximum water column stratification, in the last decade of January. Organic matter flux through the water column showed rather constant values up to the 24th of January. Immediately after, a sudden increase took place (24-29 January), reaching 13.55 g/m2/d for TSM, 0.24 g/m2/d for lipids, 0.53 g/m2/d for proteins, 0.37 g/m2/d for carbohydrates, 0.69 g/m2/d and 0.1 g/m2/d for POC and PON, respectively, 0.5 and 2.8 mg/m2/d for chlorophyll-α and phaeopigments, in correspondence to the fluorescence peak occurring in the same period. A large part of the total flux was represented by oval faecal pellets, as accounted by microscopical observations of sedimented material. Most of the pellets were 200-300 μm long, filled mainly by diatom frustules.